Survival and longevity in neotropical damselflies (Odonata, Polythoridae) (2019)
Survival and longevity in neotropical damselflies (Odonata, Polythoridae). Longevity among insect orders varies greatly, and has mainly been studied in insects in temperate biomes, where seasonality determines high synchronization of reproductive activities and limits lifespan. Most forest damselflies in tropical regions have low population densities and are almost never observed in copula. We hypothesized that selection will favour a high survival rate and hence high lifespan, allowing the animals to be ready for the occasional events that favour reproduction. We studied two neotropical damselflies, Polythore mutata and P. derivata, in Ecuador, using mark–recapture methods. We found that sex affected the rate of recapture, but daily survival rate was affected by sex only in one population. We found evidence that suggests stabilizing or directional selection on body size. The maximum lifespan was 54–63 days. We conclude that the survival rate of Polythore damselflies in tropical forests is comparable to that of similar damselflies in temperate zones. © 2019. Museu de Ciències Naturals de Barcelona. All rights reserved.